2007
DOI: 10.1002/hep.21666
|View full text |Cite
|
Sign up to set email alerts
|

Assembly and budding of a hepatitis B virus is mediated by a novel type of intracellular vesicles

Abstract: Formation of enveloped viruses involves assembly and budding at cellular membranes. In this study, we elucidated the morphogenesis of hepadnaviruses on the ultrastructural and biochemical level using duck hepatitis B virus (DHBV) as a model system. Formation of virus progeny initiates at the endoplasmic reticulum (ER) and is conserved both in vitro and in vivo. The morphogenesis proceeds via membrane-surrounded vesicles containing both virions and subviral particles, indicating a common morphogenetic pathway. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 48 publications
(59 reference statements)
3
11
0
Order By: Relevance
“…While it has been suggested that subviral particles in nonhepatocyte (MDCK) cells traffic by different routes to HBV particles (18), this would appear to be a function of the cells rather than the antigen because it is contrary to the mass export of both HBsAg and HBV virions into plasma from hepatocytes. In hepatocytes, synthesized DHBV and subviral particles have been shown to enter the same type of vesicular bodies after the endoplasmic reticulum (20), which reinforces the need to use hepatocyte-derived cells for the current studies.…”
Section: Discussionsupporting
confidence: 59%
“…While it has been suggested that subviral particles in nonhepatocyte (MDCK) cells traffic by different routes to HBV particles (18), this would appear to be a function of the cells rather than the antigen because it is contrary to the mass export of both HBsAg and HBV virions into plasma from hepatocytes. In hepatocytes, synthesized DHBV and subviral particles have been shown to enter the same type of vesicular bodies after the endoplasmic reticulum (20), which reinforces the need to use hepatocyte-derived cells for the current studies.…”
Section: Discussionsupporting
confidence: 59%
“…Thus, they may represent newly forming intermediates in either the degradation pathway or the HBV virion maturation. This is in agreement with a recent report showing assembly and budding of virion particles into a novel type of intracellular vesicles using duck HBV as a model system [23] . These vesicles derived from ER having unique identity and properties of ER, intermediate compartment, endosomes and MVB.…”
Section: Discussionsupporting
confidence: 93%
“…Some of these particles consist of empty particles with no electron-dense nucleocapsid possibly representing either defective interfering particles [27] or SVP [23] . In addition, enveloped particles with an electron-dense nucleocapsid likely corresponding to virions were observed.…”
Section: Discussionmentioning
confidence: 99%
“…The S protein plays a major role in the secretion and the budding of virus particles. Budding of surface proteins without the nucleocapsids and virus genome into the ER lumen results in the production of sub-viral particles (SVPs) [24].…”
Section: Hbv Replicationmentioning
confidence: 99%
“…Mature nucleocapsids containing rcDNA genomes are then recycled to the nucleus to form a pool of cccDNA ( Fig. 1), ranging from 30 to 50 copies of cccDNA per cell [21], or are exported from the cell via the endoplasmic reticulum (ER), where nucleocapsids are enveloped in surface proteins embedded in host-derived lipid [22][23][24].…”
Section: Hbv Replicationmentioning
confidence: 99%